Đề xuất xây dựng bộ công cụ đánh giá năng lực mĩ thuật cho học sinh lớp 6 trong dạy học Mĩ thuật - Nguyễn, Thị Hồng Thắm; Phạm, Đình Bình; Phạm , Thị Nụ (Tạp chí Giáo dục, 2024)
Testing and assessment is an essential aspect of the education process, contributing to the implementation of competency-based innovation of the general education program. In order to conduct an accurate, timely and significant assessment of artistic competence for 6th graders, the researchers have designed a number of artistic competency assessment tools for formative and summative assessment. The assessment tools proposed in the article along with the standards for evaluating artistic competency can be flexibly applied into testing and assessment, as well as organizing art teaching in order to meet requirements of the 2018 General Education Curriculum for Fine Arts.